Pengaruh Iklim Kerja Panas Terhadap Respon Fisiologis Pekerja dalam Ruang Preparasi di PT-X - fitriani, nur shabrina ulima; Natalisanto, Adrianus Inu; Sutaji Putri, Devina Rayzy Perwitasari; Mislan, Mislan; Putri, Erlinda Ratnasari (Progressive Physics Journal, 2023)
Work climate is one of the factors whose gave big influence on the performance of human resources, for both in hot work climate and cold work climate, even the effect is not limited to performance but can go further, specifically on the safety and health of workers. For this reason, it is necessary to measure and evaluate the working climate standard. This study was conducted to determine the effect of hot working climate on the physiological response of workers in the preparation room at PT-X and to find a temperature control strategy in the preparation room at PT-X. The research were carried out in 4 steps, namely: first was collecting data on the work climate in the Preparation Room at PT-X, second was collecting data on the workload of workers in the Preparation Room at PT-X, third was collecting data on the physiological response of the worker in the form of measuring body temperature, measuring blood pressure, measuring pulse rate and measuring the weight of workers. The last step was analysis. Based on the results of the research, the hot working climate affects the physiological response of the workers before and after work. The strategy for controlling the hot working climate in the Preparation Room at PT-X is by increasing the rest time for workers, maximizing the use of PPE (Personal Protection Equipment) for each worker, and adding health signs at the worker's location.